Intoxication Levels of Bar Patrons at an Organized Pub Crawl in a College Campus Community - Dodd, Virginia J. (American journal of criminal justice, 2012)
This field study examined whether participants of a traditional, end-of-semester pub crawl in a college campus community had higher levels of intoxication than non-participating bar patrons on the same night as the event. A total of 693 bar patrons participated in the study. Anonymous interview and breath alcohol concentration (BrAC) data were collected from pedestrians in a bar district at the end point of the pub crawl route between 10:00 p.m. and 3:00 a.m. on the night of the event during three different semesters (November, 2007, May, 2008, and May, 2009). A multivariate model adjusting for participant demographics and drinking variables showed that participation in the pub crawl was associated with a 70% reduced risk of being highly intoxicated (i.e., BrAC ≥ 0.08 g/210 L). The lower intoxication levels among pub crawl participants may have implications for harm reduction practices at high-risk drinking events. These implications are discussed.